Pengaruh Persepsi Siswa tentang Implementasi Pendidikan Akhlak Terhadap Perilaku Sosial - Faza Karimatul Akhlak; Nur Aini Zaida; Tsamrotul Fuadah (Prodi Pendidikan Keagamaan Islam, 2026)
This study is motivated by the fact that many students still exhibit poor social behavior, such as engaging in fights, skipping school, and showing a lack of respect toward teachers and parents. This condition indicates that the process of internalizing moral and character values in learning has not been optimally implemented. One of the factors influencing students’ social behavior is their perception of the subject of Moral and Character Education. This study employs a quantitative survey method. Data were collected from 108 respondents and analyzed using simple linear regression. The results show a significant effect, with a t-value of 4.525 greater than the t-table value of 1.983 and a significance value of 0.000 less than 0.005. This indicates that students’ perceptions of the subject significantly influence their social behavior by 16.2%, while the remaining 83.8% is influenced by other factors such as family guidance, peer influence, and academic culture.